2022
DOI: 10.1002/hep.32500
|View full text |Cite
|
Sign up to set email alerts
|

An international survey on patterns of practice in NAFLD and expectations for therapies—The POP‐NEXT project

Abstract: Background and Aims Differences between countries in NAFLD patient care pathways and management need to be understood prior to defining supranational guidelines. Approach and Results We conducted an anonymous survey in France, Germany, Hong Kong, Italy, Romania, Spain, the United Kingdom, and the United States among physicians providing specialist care for patients with NAFLD. Modalities of patient referral, patterns of practice (diagnosis, staging, monitoring, and indications for liver biopsy), therapeutic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This is in accordance with a survey by Ratziu et al., which focused on modalities of patient referral and patterns of practice. In this study, 56% of surveyed hepatologists and gastroenterologists reported that less than half of the referred NAFLD patients had tried lifestyle changes before being referred to a hepatologist 27 . In order to support physicians who are not specialised in NAFLD, it is important to update guidelines with specific lifestyle interventions and include these in educational programs.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This is in accordance with a survey by Ratziu et al., which focused on modalities of patient referral and patterns of practice. In this study, 56% of surveyed hepatologists and gastroenterologists reported that less than half of the referred NAFLD patients had tried lifestyle changes before being referred to a hepatologist 27 . In order to support physicians who are not specialised in NAFLD, it is important to update guidelines with specific lifestyle interventions and include these in educational programs.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to several earlier NAFLD surveys, 17,19,21,27 the current study focused largely on healthcare workers from specialities other than hepatologists and gastroenterologists, in particular cardiologists, internists and GPs. Moreover, the current survey also Despite the growing disease burden of NAFLD, a significant gap in awareness, knowledge and management of NAFLD remains between physicians in different fields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
To the editor, Ratziu et al's [1] fascinating survey of clinical variability in the diagnosis and management of NAFLD emphasizes the uncertain place that it occupies in the field of hepatology. Is it a liver condition or one manifestation of a metabolic disorder?
…”
mentioning
confidence: 99%